Ghoulfriends - who's that ghoulfriend? - Daneshvari, Gitty (Little, Brown and Company, 2013)
"The three ghoulfriends, Robecca Steam, Venus McFlytrap, and RochelleGoyle, are on the case to solve the mystery of the missing headmistress!"..
Keywords: JUVENILE FICTION / Media Tie-In / bisacsh; JUVENILE FICTION / Girls & Women / bisacsh; JUVENILE FICTION / Humorous Stories / bisacsh; JUVENILE FICTION / Media Tie-In; JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Humorous Stories; Kinderbuch